STRATEGI PEMERINTAH KOTA SURABAYA DALAM MEMBERIKAN PERLINDUNGAN PADA ANAK KORBAN KEKERASAN - Gina Nur Maya Jannah; Agus Widiyarta (Halu Oleo University, 2025)
This study aims to analyse the management strategy of UPTD PPA Surabaya in protecting child victims of violence. This study was conducted using a qualitative approach and case study type concerning Fred R. David's (2016) management strategy theory, which includes strategy formulation, strategy implementation, and strategy evaluation. Data collection was carried out through observation, interviews, and documentation. The results of the study indicate that UPTD PPA implements a structured strategy in handling child victims of violence, such as initial assessment, psychological and legal assistance, and the provision of safe houses. However, there are still obstacles to the quality of human resources and finances. Overall, UPTD PPA shows a strong commitment to providing protection and recovery for child victims of violence.